Cardiac Magnetic Resonance in Rheumatology to Detect Cardiac Involvement Since Early and Pre-clinical Stages of the Autoimmune Diseases: A Narrative Review - Sierra-Galan, Lilia M.; Bhatia, Mona; Alberto-Delgado, Angel Leovigildo; Madrazo-Shiordia, Javier; Salcido, Carlos; Santoyo, Bernardo; Martinez, Eduardo; Soto, Maria Elena (Frontiers in Cardiovascular Medicine, 2022)
Autoimmune diseases (ADs) encompass multisystem disorders, and cardiovascular involvement is a well-known feature of autoimmune and inflammatory rheumatic conditions. Unfortunately, subclinical and early cardiovascular involvement remains clinically silent and often undetected, despite its well-documented impact on patient management and prognostication with an even more significant effect on severe and future MACE events as the disease progresses. Cardiac magnetic resonance imaging (MRI), today, commands a unique position of supremacy versus its competition in cardiac assessment and is the gold standard for the non-invasive evaluation of cardiac function, structure, morphology, tissue characterization, and flow with the capability of evaluating biventricular function; myocardium for edema, ischemia, fibrosis, infarction; valves for thickening, large masses; pericardial inflammation, pericardial effusions, and tamponade; cardiac cavities for thrombosis; conduction related abnormalities and features of microvascular and large vessel involvement. As precise and early detection of cardiovascular involvement plays a critical role in improving the outcome of rheumatic and autoimmune conditions, our review aims to highlight the evolving role of CMR in systemic lupus erythematosus (SLE), antiphospholipid syndrome (APS), rheumatoid arthritis (RA), systemic sclerosis (SSc), limited sclerosis (LSc), adult-onset Still’s a disease (AOSD), polymyositis (PM), dermatomyositis (DM), eosinophilic granulomatosis with polyangiitis (EGPA) (formerly Churg-Strauss syndrome), and DRESS syndrome (DS). It draws attention to the need for concerted, systematic global interdisciplinary research to improve future outcomes in autoimmune-related rheumatic conditions with multiorgan, multisystem, and cardiovascular involvement.